umb and crazy?: Gender and social movements in TV fiction regarding spanish transition to democracy - Coronado, Carlota; Galán, Elena (Historia y Comunicación Social, 2015)
In the last decade, Tv’s historical fiction has become a trend and Spain has contributed with stories set in the country’s most recent past, like Franco’s regime or the transition to democracy. In TV shows like Cuentame cómo pasó or La chica de ayer, spanish society is portrayed, including political and social movements that were born in that era, among them, feminism . Though this article, the image portrayed by these series of the feminist movement and women during the transition to democracy, are analyzed.